The Expenditure Pattern on Ecotourism Resources in Taman Negara: The Case for International Tourists - Tan, Adrianne Cheryl (2002)
National Parks are under increasing pressure to provide economic justification for their existence, particularly in developing countries where demand for land and natural resources is high. Ecotourism offers a mechanism to generate substantial benefits from protected areas for governments and local communities, as well as the private investors. Also, ecotourism is increasingly promoted as a sustainable use of such protected areas through generation of income and revenue for the nation. This study was aimed at (1) analyzing international tourists' expenditure patterns in Taman Negara using model comparison for individual total expenditure, average group expenditure and individual daily expenditure. (2) examining the consumer preferences and tastes for nature-based outdoor recreation activities (3) find out the international tourists' feedback on the recreational attributes, current status of recreational facilities and services provided. (4) determining the international tourists' socio-economic characteristics and their distribution. A total of 384 respondents were interviewed using close-ended questionnaires. Collected data were analyzed using descriptive analysis, index analysis, factor analysis, correlation analysis, multiple regression analysis, F statistic test and t-test. The findings identified Europeans as having the highest percentage of respondents whose age were between 21-30 years old. Most of the respondents were university graduates and earn between USD 1001 to 2000 per month. Male participation is higher when compared to female and most of the respondents led a single life. More than half of the respondents agreed with the recreational attributes in Taman Negara. Meanwhile, more than 600/0 of the respondents thought that little improvement is needed for all the current services and facilities provided except for road transportation, information and access to recreational facilities such as jungle tracks and canopy walkway within the park which were highly recommended for improvement. Our result indicated that there were five recreational activities namely canopy walkway, jungle trekking, night walk, wildlife observation and visiting Lata Berkoh that were highly participated, preferred and popular among the international tourists. There were various price levels that the international tourists spent for the three basic important elements namely: accommodation , food and recreational activity during their stay in the park. The highest price that they paid for accommodation was between RM61 to RM80 per day per person. Respondents also revealed their expenditure for recreational activities participated in the park. Meanwhile, they spent less for food, which was about RM2 1 to RM40 per day per person. Eight independent variables were chosen to explain the tourist expenditures. These eight independent variables consisted of income, age, education level, region, satisfaction level for the top five recreation activities, length of stay, marital status and travelling pattern. The dependent variables were individual total expenditure, average group expenditure and individual daily expenditure. Although all independent variables showed different influences in the three different functional forms, some similarities were observed in this study. For example, region, income, satisfaction level for top five recreation activities and travelling pattern were found significant but inelastic. The explanation from the result indicate that although these variables do influenced the dependent variables but the impact is very small in affecting the respondents' decision making for their expenditure pattern in the park. Meanwhile, age, education level, length of stay and marital status were statistically insignificant. Besides that, log-linear form model was selected as the basis for further evaluation and analysis focusing on the international tourists expenditure pattern in Taman Negara.